An Assessment of Plant Growth and Soil Properties Using Coal Char and Biochar as a Soil Amendment - Resham B. Thapa; Roger H. Coupal; Mohan B. Dangi; Peter D. Stahl (Agronomy, 2024)
Soil degradation due to loss of soil organic carbon is a serious concern in semiarid agroecosystems. Biochar and other organic char products have long been known to increase soil organic carbon. In this study, three-year field observations were carried out on use of coal char (CC) and biochar (BC) as soil amendments in unirrigated semiarid rangeland soil. Coal was pyrolyzed at three different temperatures of 650, 750, and 800 °C to form CC650, CC750, and CC800, respectively, and BC was obtained from a local commercial producer. Manure, CC, and BC were incorporated in soil at 10% (v/v). Analyses of plant growth (aboveground biomass) and soil properties were performed and compared with the control treatment without char. In all three years, CC applied with manure (CC650M) produced significantly greater grass biomass, by 95, 42, 101%, and BC applied with manure (BCM) increased grass biomass by 89, 39, 52% in 2018, 2019, and 2020, than the controls in the respective years. Soil tests a year after application of char indicated significantly increased soil organic matter (OM) with CC and BC treatments (1.60–2.93%) compared with the control (1.37%). However, further detailed studies are required to investigate CC and BC interactions with soil in unirrigated semiarid rangelands.